Indian Pharmaceutical Product Protection by Utilizing Intellectual Property Rights - Krishna, Pasupuleti Dheeraj; Sujatha, Deeksha Kethareshwara; Veeranna, Balamuralidhara (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Intellectual property rights (IPR) are described as concepts, creations, especially artistic endeavors around which the community is ready to confer the position of ownership. There are various sorts of intellectual property protection such as patents, copyright, trademarks, and so on. A patent is an acknowledgment of an innovation that meets the standards of worldwide uniqueness, non-obviousness, as well as commercial use. It is required for improved identifying, organizing, marketing, and rendering, and hence for the ownership of innovation or creation. Apart from copyright, which is worldwide in the meaning that it is instantly available in all Berne Convention members. It is crucial to note that, with the exception of copyright and trade secrets, all rights must be renewed on a regular basis in order to remain in effect. Aim: The goal of this work is to study the ways to protect pharmaceutical product by utilizing IPR. Materials and Methods: This study has been performed by gathering information from the official websites if IPR. Results: IPR, like every commodity, may be transferred, donated, sold, and licensed. An institution which is not independent may be unable to possess intellectual property. Improvements and modifications made to well-known items can be safeguarded. However, geographical indications might be used to safeguard particular agricultural as well as historical items. Conclusion: Apart from trademarks and geographical indications, that can have an indefinite life if reissued after a certain time period by submitting official fees, IPR have a fixed term.
Keywords: Drug protection; Intellectual property; License; Patent; Pharmaceutical; protection; IPR